Discretionary Authority Of Law Enforcement Officials In The Settlement Of Criminal Cases Based On Restorative Justice - Deny; Eko Budi Sariyono; Iwan Rasiwan; Johannes Triestanto; Zulkarnain S (Universitas Muhammadiyah Palu, 2026)
Discretion exercised by law enforcement officials constitutes an inherent authority within the law enforcement function to make decisions or take actions based on professional judgment, particularly in circumstances that are not comprehensively regulated by statutory provisions. In the development of modern criminal law, discretionary power has gained increasing relevance, especially when associated with the application of a restorative justice approach that emphasizes victim recovery, offender accountability, and the restoration of social harmony within the community. This article aims to examine the scope of discretionary authority held by law enforcement agencies in resolving criminal cases through a restorative justice framework in Indonesia. The discussion focuses on the factors that encourage the use of discretion, the normative and ethical limitations governing its application, the roles of various law enforcement institutions within the criminal justice system, as well as the challenges encountered in practical implementation. The research employs a normative juridical approach, utilizing library-based data collection methods through the analysis of statutory regulations, legal doctrines, and relevant national legal journal publications. The data are analyzed using a descriptive-analytical method to assess the alignment between legal norms and law enforcement practices. The findings indicate that law enforcement discretion can serve as an effective instrument in supporting the implementation of restorative justice, particularly in certain criminal cases with limited social impact. Nevertheless, the effectiveness of discretionary practices is highly dependent on the consistent application of prudential principles, proportionality, legal certainty, utility, and participatory transparency involving victims, offenders, and the community. In the absence of clear guidelines and adequate oversight mechanisms, the exercise of discretion may lead to legal uncertainty and unequal justice. Therefore, strengthening regulatory frameworks and enhancing the capacity of law enforcement personnel are essential prerequisites for optimizing discretion within a restorative justice-based criminal justice system.